Large Losses from Little Lies: Randomly Assigned Opportunity to Misrepresent Substantially Lowers Later Cooperation and Worsens Income Inequality - Michalis Drouvelis; Jennifer Gerson; Nattavudh Powdthavee; Yohanes E. Riyanto (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Social media has made anonymized behavior online a prevalent part of many people's daily interactions. The implications of this new ability to hide one's identity information remain imperfectly understood. Might it be corrosive to human cooperation? This paper investigates the possibility that a small deceptive act of misrepresenting some information about one's real identity to others – a social media-related behavior commonly known as 'catfishing' – increases the likelihood that the individual will go on to behave uncooperatively in an otherwise anonymous prisoner's dilemma game. In our intention-to-treat analysis, we demonstrated that randomly allowing people to misrepresent their gender identity information reduced the aggregate cooperation level by approximately 12-13 percentage points. Not only that the average catfisher was substantially more likely to go on to defect than participants in the control and the true gender groups, those who were paired with a potential catfisher also defected significantly more often as well. Participants also suffered a significant financial loss from having been randomly matched with a catfisher; 64% of those who played against someone who chose to misrepresent information about their gender received a payoff of zero from the prisoner's dilemma game. Our results suggest that even small short-term opportunities to misrepresent one's identity to others can potentially be extremely harmful to later human cooperation and the economic well-being of the victims.
Keywords: C92; D91; 330; cooperation; misrepresentation; social media; social dilemma; experiment